2019
DOI: 10.1002/prca.201800155
|View full text |Cite
|
Sign up to set email alerts
|

Matrix‐Metalloprotease Resistant Mucin‐16 (MUC16) Peptide Mutants Represent a Worse Lung Adenocarcinoma Outcome

Abstract: Purpose: The relationship of lung adenocarcinoma (LUAD)-specific proteases and the mutant profile of cytoskeletal and extracellular matrix proteins (CECMPs) are examined. Experimental design: Mutant CECMPs are assessed with an automated application of a protease binding, amino acid-based, scoring database. Results: MUC16 (Human Genome Organization symbol for mucin-16 gene) mutants in particular are, more often than not, resistant to matrixmetalloproteases (MMPs) commonly secreted by LUAD cells, and LUAD cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…These variations are nonsynonymous in nature and may change the structural integrity of the barrier. Several studies have reported on the role of MUC16 in different types of cancers including breast cancer [ 36 , 37 , 38 , 39 , 40 ]. As these alterations are germline variations, we hypothesize that, in breast cells they may have allowed the uptake/release of cell-signaling molecules leading to initiation/blockage of signaling pathways, subsequently triggering tumor development and progression at an early age in these women.…”
Section: Discussionmentioning
confidence: 99%
“…These variations are nonsynonymous in nature and may change the structural integrity of the barrier. Several studies have reported on the role of MUC16 in different types of cancers including breast cancer [ 36 , 37 , 38 , 39 , 40 ]. As these alterations are germline variations, we hypothesize that, in breast cells they may have allowed the uptake/release of cell-signaling molecules leading to initiation/blockage of signaling pathways, subsequently triggering tumor development and progression at an early age in these women.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic monoclonal antibody is generally effective in the extracellular region, and the dissociation of the extracellular region leads to the loss of target; on the other hand, the MUC16 gene fragment is relatively long and has a high mutation rate 37,44 . Some mutant strains can promote MUC16 expression 24 and even have a higher tumorigenic effect than that of the original target change 39,51 . We confirmed that ERO1L was a key factor upstream of MUC16 that significantly affected MUC16 expression.…”
Section: Discussionmentioning
confidence: 99%
“…A MUC16-mutant was resistant to matrix-metalloproteases (MMPs) that were released by LUAD cells. Furthermore, LUAD with both MMP-and MUC16-resistant mutant expression had an unfavourable prognosis [45]. e overexpression of MUC16 was correlated with familial lung cancer, air pollution produced by coal indoor, higher metastasis, and an advanced stage.…”
Section: Mucs In Nsclcmentioning
confidence: 98%